Constraints Faced by the Members of Dairy Co-operative Societies in Receiving the Services of Dairy Union - Shivpal Kumhar , Sangram Singh; M. K. Jangid (Indian Journal of Extension Education, 2013)
Although India ranks the world’s the largest milk producer, our per capita milk consumption is one of the lowest in the world. It implies that it is not only the improvement of genetic potential of milch animals which could increase the milk production, but there are other factors also which need attention so far as milk production is concerned. The present study was conducted in Jaipur district of Rajasthan. Jaipur district was selected purposively. A sample of 144 respondents, consisting of 72 members of dairy co-operative societies and 72 non-members of dairy co-operative societies was drawn. The respondents for study group were selected randomly from 24 dairy co-operative societies of 12 randomly selected randomly milk procurement routes. Whereas, non-members were also selected randomly from village of the same dairy co-operative societies. The data were collected with the help of pre-tested structured interview schedule. The least important constraints perceived by the dairy cooperative society members were irregular visit of mobile team of veterinary doctors for treatment of sick animals, lack of awards and recognition given by dairy union for motivation of dairy members and there was no provision of loans for cattle purchasing by society and union in the research area.